2007
DOI: 10.3354/meps331049
|View full text |Cite
|
Sign up to set email alerts
|

Trophic heterogeneity in salt marshes of the northern Gulf of Mexico

Abstract: Predator-prey interactions in salt-marsh ecosystems are driven primarily by interactions among tidal dynamics, local physiography, and macrophyte density. Distinct seaward-to-landward predation gradients have been described for the continuous and expansive meadows of Spartina alterniflora on the Atlantic coast of the United States. In the northern Gulf of Mexico, Juncus roemerianus dominates and Spartina is generally limited to fringing bands or disjunct patches in low-lying areas. It is not known whether pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Although it must be recognised that repair scars represent failed attacks and are thus analogous to incomplete rather than complete drill holes (Vermeij 1987;Allmon et al 1990;Leighton 2001Leighton , 2002Harper 2006), they can be used as proxy for predatory activity. This is supported by a recent study with live blue crabs and periwinkles by Moody and Aronson (2007) which demonstrated that the occurrence of sublethal shell repair in Littorina was positively correlated with the frequency of predatory attacks and the abundance of crabs.…”
Section: Introductionsupporting
confidence: 72%
“…Although it must be recognised that repair scars represent failed attacks and are thus analogous to incomplete rather than complete drill holes (Vermeij 1987;Allmon et al 1990;Leighton 2001Leighton , 2002Harper 2006), they can be used as proxy for predatory activity. This is supported by a recent study with live blue crabs and periwinkles by Moody and Aronson (2007) which demonstrated that the occurrence of sublethal shell repair in Littorina was positively correlated with the frequency of predatory attacks and the abundance of crabs.…”
Section: Introductionsupporting
confidence: 72%
“…1982; Warren 1985; Schindler et al. 1994; Lewis & Eby 2002; Silliman & Bertness 2002; Moody & Aronson 2007). Blue crabs invade the marsh with flood tides and prey on Littoraria that migrate upward from the sediment surface along Spartina stems during flood tides, typically returning to open‐water areas and tidal creeks on ebbing tides.…”
Section: Problemmentioning
confidence: 99%
“…Tidal estuaries are unique environments where a distinct array of physical and chemical properties can vary over relatively short time periods (Dardeu et al 1992) and small distances (Mannino and Montagna 1997). Predicting the response of estuarine ecosystems to changing environmental conditions is therefore challenging, as it necessitates understanding interactions among several trophic levels and multiple nutrient sources (marine, freshwater, and terrestrial) (Day et al 1993;Moody and Aronson 2007). Because birds are relatively well studied, they have been used to measure ecological conditions and evaluate the impacts of environmental change within tidal estuaries (Shriver et al 2004;DeLuca et al 2008).…”
Section: Introductionmentioning
confidence: 99%